THE ROLE OF PARENTS IN CHARACTER-SHAPING CHILDREN AGED 4-6 IN PENUNTUT JANAPRIA VILLAGE - Dini Septi Harianti (JOETAL: Journal of Education, Teaching and Learning, 2025)
This research is motivated by a phenomenon discovered by the researcher, where children aged 4-6 in Penuntut Hamlet, Janapria District, exhibit polite and courteous speech, using refined or polite regional language in their daily activities. Considering the reality of today's modern era, many children are also experiencing a decline in manners and politeness towards their elders, or even less polite language. The aim of the research is to find out the role of parents in shaping the character of children aged 4-6 years in Penuntut Hamlet, Janapria and also to find out its supporting and inhibiting factor. Data collection techniques were conducted using combined triangulation. Data analysis is inductive or qualitative, and qualitative research results emphasize meaning over generalization. The method used in this study is qualitative, which aims to describe the situation objectively through words and sentences. the data analysis used the Miles and Huberman model. The researcher used data triangulation to test the validity of the data in this study. The results of this study indicate that the role of parents in shaping and educating children's character is crucial. This study identifies four types of parental roles: educators, guides, motivators, and facilitators.